Techniques For Increasing Solubility: A Review Of Conventional And New Strategies - Yadav, Keerti; Sachan, Anupam Kr.; Kumar, Sunil; Dubey, Anubhav (Asian Journal of Pharmaceutical Research and Development, 2022)
Whenever a drug’s success depends on its ability to disperse evenly in the liquid phase, solubility is a critical factor. Most active pharmacological compounds, on the other hand, are poorly soluble in water. The solubility of the medications is one of the most difficult parts of formulation creation. Due to a lack of water solubility, critical ingredients are left out of final medications, preventing them from reaching their full therapeutic potential. Due to poor water solubility, many novel medicines fail to launch in the market, despite their promising pharmacokinetic properties. Solubility in water limits the potential bioavailability of molecules that would otherwise have a significant impact on their physiological target. To achieve the desired (anticipat5ed) pharmacological response in the systemic circulation, aqueous solubility of a drug also affects the physical, chemical, dose stability, severs as a standard for purity, dissolution rate, rate and extent of absorption, and achieves the desired concentration of the drug in systemic circulation. When it comes to the formulation of medications, solubility is an extremely essential issue. A new API with high market demand must be developed by the formulation scientist if the molecule is to make it through the pharmaceutical development process. Solubilization techniques, such as chemical modification using solubilizers such as soluplus, povacoat, and dendrimers, as well as physical modification, complexation, and the use of surfactant, are being discussed in this review article because they are becoming increasingly important to the pharmaceutical industry by opening up new pathways for the preparation of effective and marketable drugs.